Sialomucin CD43 Plays a Deleterious Role in the Development of Experimental Heart Failure Induced by Pressure Overload by Modulating Cardiac Inflammation and Fibrosis - Kaur, Kuljeet; Velázquez, Francisco E.; Anastasiou, Marina; Ngwenyama, Njabulo; Smolgovsky, Sasha; Aronovitz, Mark; Alcaide, Pilar (Frontiers in Physiology, 2021)
Sialomucin CD43 is a transmembrane protein differentially expressed in leukocytes that include innate and adaptive immune cells. Among a variety of cellular processes, CD43 participates in T cell adhesion to vascular endothelial cells and contributes to the progression of experimental autoimmunity. Sequential infiltration of myeloid cells and T cells in the heart is a hallmark of cardiac inflammation and heart failure (HF). Here, we report that CD43−/− mice have improved survival to HF induced by transverse aortic constriction (TAC). This enhanced survival is associated with improved systolic function, decreased cardiac fibrosis, and significantly reduced T cell cardiac infiltration in response to TAC compared to control wild-type (WT) mice. Lack of CD43 did not alter the number of myeloid cells in the heart, but resulted in decreased cardiac CXCL10 expression, a chemoattractant for T cells, and in a monocyte shift to anti-inflammatory macrophages in vitro. Collectively, these findings unveil a novel role for CD43 in adverse cardiac remodeling in pressure overload induced HF through modulation of cardiac T cell inflammation.